Microzooplankton and the plankton food web in the subtropical frontal region of the Indian Ocean sector of the Southern Ocean during austral summer 2012. (August 2020) - Devi, C.R. Asha; Sabu, P.; Naik, R.K.; Bhaskar, P.V.; Achuthankutty, C.T.; Soares, M.; Anilkumar, N.; Sudhakar, M.
Abstract: The Southern Ocean is a very dynamic ecosystem comprising many fronts and interfrontal areas. Among the fronts, the Subtropical Front (STF) is a region of eddy activity exhibiting high spatial-temporal variability. The variability of food web structure in such a dynamic system and their influence on the plankton community structure is of great interest. The present study attempts to explain the variability of microzooplankton (MZP) mediation in the planktonic food web, using multi-disciplinary data collected along the zonal sections 40° S and 43° S in the STF during the austral summer 2012. Even though both zonal sections are in the STF, significant differences in the variability of their thermohaline structures were observed due to the presence of multiple mesoscale features (viz. cyclonic and anticyclonic eddies), leading to discrete environments within the STF. Our study highlights the concept of the classical food web in productive environments (cyclonic eddies), which is governed by the duration of such dynamic events. On the contrary, in the generally less productive anticyclonic eddies, the variability of trophic level interaction varies between the periphery and core regions of the eddies. The present study reveals the biological consequences of frequent mesoscale features in terms of the variability of food web structure. It also elucidates the trophic importance of MZP in the two contrasting environments within the STF.